Organic Corrosion Inhibitors for Aluminium in Sodium Hydroxide - Maayta, A.K. (Asian Journal of Chemistry, 2010)
Inhibition of corrosion of aluminium in aqueous solutions of sodium hydroxide in the presence of sulfonic acid, sodium cumene sulfonate and sodium alkyl sulfate was studied in relation to the concentration of inhibitor and concentration of corrosive medium at various temperatures applying weight loss method. The additives tested were found to be good inhibitors for aluminium corrosion in aqueous solutions of sodium hydroxide in the studied concentration range. Due to the adsorption of the additive molecules on the metal surface the inhibition efficiency increases with increasing additive concentration, Sulfonic acid shows the best inhibition capability for aluminium corrosion in sodium hydroxide; probably, this is due to the planar orientation of the adsorbed additive molecules. Inhibition efficiency of the inhibitors tested increases with decreasing sodium hydroxide concentrations. The higher the temperature, the lower was the inhibition efficiency, which is due to the fact that the rate of corrosion of aluminium is higher than the rate of adsorption.